Building a Sales Network for Small Businesses in East Java Province, Indonesia - I Putu Artaya; R Agus Baktiono; Made Kamisutara; IGA Sri Deviyanti; Sulistyani Eka Lestari (LPPM of NAROTAMA UNIVERSITY, 2021)
Local and global economic activities which are increasingly supported by the development of increasingly advanced information technology will certainly have a good impact on the development of a local economy that is with the livelihood and development of micro and small business activities in a region or country. Such conditions must be well anticipated by all small businesses to take advantage of these technological advancements for future business development. There are many critical factors for the success of a business actor in carrying out his business mission, but with technological advancements, the gap to utilize technology properly is the key to success in itself, bearing in mind that the world is now in an all-digital communication order. Increasingly being able to adopt advanced technology, will certainly bring its own success for business people. This research was conducted on a group of small businesses in Indonesia who began to pioneer their businesses by utilizing information technology in cooperating with business partners and customers in order to enter the global market.